Enhancing Career Exploration in High School Students in Pandeglang Through Interactive Video Media: A Development and Validation Study - Devi Nurul Fikriyani; Ervi Nurafiliyan Susanti (G-Couns: Jurnal Bimbingan dan Konseling, 2026)
Career exploration is a critical developmental task for high school students, yet many adolescents in rural and underserved areas lack access to engaging, structured, and contextually relevant career information. This study aimed to develop and validate interactive video-based career information media to enhance career exploration among eleventh-grade students in Pandeglang, Indonesia. A Research and Development approach employing the ADDIE model was used, involving needs analysis, design, development, implementation, and evaluation stages. A total of 613 students participated in the needs assessment, followed by expert validation and field trials. The instrument demonstrated high validity and reliability. Expert validation yielded a feasibility score in the very good category, confirming the media's quality across content accuracy, instructional design, and technical aspects. Small-scale and large-scale trials showed consistent improvements in students' career exploration scores, with positive responses from both students and guidance counselors regarding the media's engagement and usability. The findings indicate that interactive video media effectively enhance students' self-awareness, understanding of career options, and active engagement in career exploration activities. This study contributes a validated, innovative, and scalable tool for school guidance and counseling services, particularly in regional contexts. Future research should employ experimental designs, examine long-term career outcomes, and adapt the media for broader educational settings. Keywords: ADDIE model, career exploration, career information media, high school students, interactive video